Masked threshold for noise bands masked by narrower bands of noise: effects of masker bandwidth and center frequency - Taghipour, Armin; Moore, Brian C. J.; Edler, Bernd (Journal of the Acoustical Society of America, 2016)
This paper examines how masked thresholds depend on the masker bandwidth and center frequency when the masker has a smaller bandwidth than the signal. The signal bandwidth was equal to the equivalent rectangular bandwidth of the auditory filter and the masker bandwidth was 0.1, 0.35, or 0.6 times the signal bandwidth. The masker and signal were centered at the same frequency of 257, 697, 1538, 3142, or 6930 Hz. Masked thresholds were estimated using a two-interval two-alternative forced-choice paradigm and a three-down one-up adaptive staircase method. Masked thresholds increased with increasing masker bandwidth and were lowest for medium center frequencies.<br